JOM FMIPA Volume 1 No. 2 Oktober 2014 450 RESPONS PERTUMBUHAN ANAKAN NYAMPLUNG (Calophyllum inophyllum L.) PADA KONDISI PENGGENANGAN DENGAN MEDIA TANAH MINERAL DAN TANAH GAMBUT - Indah Permatasari; Siti Fatonah; Dyah Iriani (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
The research on the growth response of nyamplung seedlings (Calophyllum inophyllum L.) with flooding in the mineral soil and peat soil had been conducted at the Laboratory of Botany, Department of Biology, Faculty of Mathematics and Natural Sciences, University of Riau, from December to January 2014. The purpose of this study was to test the ability of nyamplung to grow with flooding using the mineral soil and peat soil. This study used randomized block design with one factor (flooding) and five replicates, the height of inundation was 2 cm above the soil surface. The results indicated that nyamplung might grow in the mineral soil with flooding, the precentage of plant damage was 20% whereas in peat soil with flooding, nyamplung could not grow and 100% had plant damage.